Gamification and attitudes in engaging children in the learning process: A case of online math games - Hammadi, Nawal Qasim; Mohadat, May Ahmad; Alawamreh, Ali Ratib (Edelweiss Applied Science and Technology, 2024)
Over the years, children’s mathematics performance is becoming a prime focus of concern due to the continuously changing culture of education. This specific research investigates with particular attention the modern sphere of online math games and how they could change the very nature of children’s participation in this academic discipline as well as the way it is perceived. Focusing on the interaction’s perspective, this study aims at investigating the effect of attitudes together with gamification on children’s academic achievement. The primary goal of this research is to examine, within the context of the educational system of Jordan, the contribution of the intensity of use of online math games to the understanding of the relationship between theoretical and practical elements of mathematics. The subsequent findings provide valuable knowledge on how to incorporate technology and gamification for positive changes in attitude towards mathematics, which in turn leads to improved performance in the subject.